Physical fitness in young top level table tennis players: differences between sex, age and playing style - Francisco Pradas de la Fuente; Víctor Toro-Román; Miguel Ángel Ortega-Zayas; Alejandro Moreno-Azze (Frontiers in Sports and Active Living)
Understanding the physical fitness of table tennis (TT) players could be interesting in improving the training process and evaluating talent. This study aimed to assess the physical fitness of U14 TT players and differentiate between sex, age and playing style. A total of 352 players (203 males and 149 females) aged between 9 and 13 years participated in the present study. Furthermore, the sample was divided according to playing style: offensive (OFF) and mixed + defensive (M + D). A battery of tests was carried out to assess cardiorespiratory capacity, speed, strength, flexibility and power. Both sexes reported significant differences in cardiorespiratory capacity and speed (p < 0.05). Concerning age, there were substantial differences in cardiorespiratory capacity, speed, strength and power, with older players obtaining better results (p < 0.05). Finally, concerning playing style, differences were reported in cardiorespiratory capacity, higher in OFF style group, and flexibility, higher in the M + D style group. Finally, there were relationships between playing style and cardiorespiratory fitness and flexibility. Physical fitness evolves with increasing age as a function of sex. This is the first study to assess fitness in a large sample of TT players as a function of playing style.